Obstructive sleep apnea in adults with Down syndrome. Issue 12 (10th September 2020) - Landete, Pedro; Soriano, Joan B.; Aldave, Beatriz; Zamora, Enrique; Acosta, Carmen; Erro, Marta; López Riolobos, Cristina; Ramos, M. Inmaculata; Moldenhauer, Fernando; Ancochea, Julio
Abstract: Patients with Down syndrome (DS) often have a high occurrence of obstructive sleep apnea‐hypopnea (OSA) syndrome. We studied a large cohort of adults with DS attended due to clinical suspicion of OSA. A standardized questionnaire and full medical assessment were conducted, including a sleep study. One hundred and fifty‐seven DS individuals were studied, with a mean ±  SD age of 36 ± 10 years, 40.7% women, BMI 29.4 ± 5.6 kg/m 2 . The main clinical symptom was daytime sleepiness (64.9%). A sleep study was conducted in 114 patients. All 114 DS patients were diagnosed with OSA, with a predominance of obstructive and hypopnea events, (apnea‐hypopnoea index, AHI, 35.0 ± 26.6), with an oxygen desaturation index of 32.9, and a Tc90% of 24.7%. Continuous positive airway pressure (CPAP) treatment was implemented in 75 (65.8%) of subjects. Tolerance was considered good in 75% of them, with a high compliance of 79.2% >4 hr/day (mean 7.1 hr/day), resulting in a symptomatic improvement in 58.7% of them. Obstructive sleep apnea is frequently confirmed in patients with DS when it clinically suspected. Treatment with CPAP in DS is feasible, and with higher adherence than in adults with normal cognitive functioning.